تأثير مراكز البحث والتفكير على توجهات التفكير الإستراتيجي الأمريكي اتجاه الصين - ساعد, رشيد (revue mofakir; No 13 (2016): مجلـــة المفكــر, 2018)
‫‪‫‪Think‬‬ ‫‪Tanks‬‬ ‫‪as‬‬ ‫‪an‬‬ ‫‪important‬‬ ‫‪player‬‬ ‫‪in‬‬ ‫‪society‬‬ ‫‪of‬‬ ‫‪american‬‬ ‫‪strategy‬‬ ‫‪for‬‬ ‫‪the‬‬ ‫‪homeland‬‬ ‫‪security‬‬ ‫‪signify‬‬ ‫‪to‬‬ ‫‪what‬‬ ‫‪extant‬‬ ‫‪this‬‬ ‫‪organized‬‬ ‫‪group‬‬ ‫‪of‬‬ ‫‪institutes‬‬ ‫‪influence‬‬ ‫‪on‬‬ ‫‪the‬‬ ‫‪environment‬‬ ‫‪of‬‬ ‫‪making‬‬ ‫‪america‬‬ ‫‪strategy‬‬ ‫‪.‬‬ ‫‪In‬‬ ‫‪this‬‬ ‫‪context‬‬ ‫‪Richard‬‬ ‫‪Haass‬‬ ‫"‪said:‬‬ ‫‪The‬‬ ‫‪research‬‬ ‫‪center‬‬ ‫‪and‬‬ ‫‪Policy‬‬ ‫‪Stady‬‬ ‫‪become‬‬ ‫‪the‬‬ ‫‪most‬‬ ‫‪important‬‬ ‫‪and‬‬ ‫‪the‬‬ ‫‪less‬‬ ‫"‪estimation.‬‬ ‫‪The‬‬ ‫‪effect‬‬ ‫‪of‬‬ ‫‪Think‬‬ ‫‪Tanks‬‬ ‫‪On‬‬ ‫‪the‬‬ ‫‪Directions‬‬ ‫‪–Orientations-‬‬ ‫‪of‬‬ ‫‪America‬‬ ‫‪Strategy‬‬ ‫‪Thinking‬‬ ‫‪award‬‬ ‫‪China‬‬ ‫‪apears‬‬ ‫‪in‬‬ ‫‪two‬‬ ‫‪strategies.‬‬ ‫‪The‬‬ ‫‪First‬‬ ‫‪is‬‬ ‫‪called‬‬ ‫‪the‬‬ ‫‪Containment‬‬ ‫‪strategy‬‬ ‫‪the‬‬ ‫‪apply‬‬ ‫‪the‬‬ ‫‪cold‬‬ ‫‪war‬‬ ‫‪strategy‬‬ ‫‪on‬‬ ‫‪china‬‬ ‫‪because‬‬ ‫‪it‬‬ ‫‪threaters‬‬ ‫‪to‬‬ ‫‪become‬‬ ‫‪a‬‬ ‫‪bigger‬‬ ‫‪power‬‬ ‫‪in‬‬ ‫‪the‬‬ ‫‪world‬‬ ‫‪agains‬‬ ‫‪to‬‬ ‫‪US.‬‬ ‫‪Frome‬‬ ‫‪the‬‬ ‫‪other‬‬ ‫‪side‬‬ ‫‪the‬‬ ‫‪second‬‬ ‫‪is‬‬ ‫‪called‬‬ ‫‪the‬‬ ‫‪Engagement‬‬ ‫‪strategy‬‬ ‫‪that‬‬ ‫‪support‬‬ ‫‪the‬‬ ‫‪boff‬‬ ‫‪integration‬‬ ‫‪of‬‬ ‫‪china‬‬ ‫‪in‬‬ ‫‪international‬‬ ‫‪institutions‬‬ ‫‪group‬‬ ‫‪work‬‬ ‫‪to‬‬ ‫‪stop‬‬ ‫‪any‬‬ ‫‪china‬‬ ‫‪ambtion‬‬ ‫‪that‬‬ ‫‪aim‬‬ ‫‪the‬‬ ‫‪basics‬‬ ‫‪of‬‬ ‫‪international‬‬ ‫‪onal‬‬ ‫‪actual‬‬ ‫‪regime.‬‬